Is the Effectiveness of Acellular Pertussis Vaccine in Pre-Adolescents Insufficient? - Lake, Noelle (MD Conference Express, 2011)
A retrospective, single-center chart review of the 2010 Bordetella pertussis outbreak in California, USA found that a time interval greater than 3 year since vaccination with acellular pertussis correlated with increased risk for acquiring the disease.